Effects of Supplementing Intestinal Autochthonous Bacteria in Plant-Based Diets on Growth, Nutrient Digestibility, and Gut Health of Bullfrogs (Lithobates catesbeianus) - Wang, Zhe; Zhang, Chunxiao; Lu, Kangle; Song, Kai; Li, Xueshan; Wang, Ling; Rahimnejad, Samad (Frontiers in Microbiology, 2021)
Poor utilization efficiency of plant protein diets always leads to intestinal barrier dysfunction and growth inhibition in animals. Probiotics have shown promise in improving growth performance and gut health of the host. However, obtaining the host-beneficial probiotic from thousands of bacterial phylotypes is challenging. Here, four intestinal autochthonous bacteria were isolated from fast-growing bullfrog after a 60-day feeding on a soybean meal (SM)-based diet. Another feeding trial was conducted to evaluate the effects of supplementing these strains in an SM-based diet on growth, nutrients digestibility, immunity, and gut health of bullfrog. A high-SM basal diet was used as a non-supplemented control group (NC), and four other diets were prepared by supplementing the basal diet with 1 × 107 CFU/g of Bacillus siamensis (BS), Bacillus tequilensis (BT), Bacillus velezensis (BV), and Lactococcus lactis (LL). Results showed that weight gain, feed efficiency, nitrogen retention, and apparent digestibility coefficients of dry matter and protein were significantly higher in the LL group compared to the NC group (P < 0.05). Furthermore, compared to the NC group, both BT and LL groups showed markedly higher jejunal protease and amylase activities, serum complement 4 and immunoglobulin M levels, jejunal muscularis thickness (P < 0.05), and upregulated expression of il-10 and zo-1 genes (P < 0.05). High-throughput sequencing revealed higher abundances of Bacillus and Cetobacterium in BT and LL groups, respectively, accompanied with decreased abundances of Enterobacter and Escherichia-Shigella. Besides, KEGG pathways related to metabolisms were significantly enhanced by the LL diet relative to the NC diet (P < 0.05). Overall, the beneficial effects of two frog-derived probiotics were determined: supplementation of L. lactis in SM-based diet promoted growth and nutrients digestibility; both B. tequilensis and L. lactis supplementation improved immune response and intestinal barrier function of bullfrogs.